Effects of alloying, microstructure and texture on the strength–ductility trade-off in layered aluminum. Issue 1 (1st July 2022) - Xia, Y P; Wu, H; Miao, K S; Geng, L; Fan, G H; Yu, T; Juul Jensen, D
Abstract: Tailoring constituent layers can lead to improved mechanical properties of layered metals. In this work, we designed and fabricated two samples of layered Al. One sample with AA3003 and AA1060 layers and the other with only AA1060 layers. The effects of these designs on the deformation behaviors are revealed by in-situ monitoring of the local strain evolution. It was found that larger microstructural and textural variations can lead to a larger difference in transverse compressive strain between constituent layers under uniaxial tension, which indicates more significant defomation incompatibility and thus a larger strain gradient caused by the constraint effect. The effects of the texture on the transverse compressive strain levels was analysed by the Lankford values calculated by the visco-plastic self-consistent method. Furthermore, the fracture behaviors of the two samples are compared and discussed based on the cross-sectional fracture morphologies. This work illustrates the potential of tailoring layered metals for a superior strength–ductility combination.